DNMT3b/OCT4 expression confers sorafenib resistance and poor prognosis of hepatocellular carcinoma through IL-6/STAT3 regulation - Lai, Ssu-Chuan; Su, Yu-Ting; Chi, Ching-Chi; Kuo, Yung-Che; Lee, Kam-Fai; Wu, Yu-Chih; Lan, Pei-Chi; Yang, Muh-Hwa; Chang, Te-Sheng; Huang, Yen-Hua (Journal of experimental & clinical cancer research, 2019)
The inflammatory cytokine interleukin-6 (IL-6) is critical for the expression of octamer-binding transcription factor 4 (OCT4), which is highly associated with early tumor recurrence and poor prognosis of hepatocellular carcinomas (HCC). DNA methyltransferase (DNMT) family is closely linked with OCT4 expression and drug resistance. However, the underlying mechanism regarding the interplay between DNMTs and IL-6-induced OCT4 expression and the sorafenib resistance of HCC remains largely unclear. HCC tissue samples were used to examine the association between DNMTs/OCT4 expression levels and clinical prognosis. Serum levels of IL-6 were detected using ELISA assays (n = 144). Gain- and loss-of-function experiments were performed in cell lines and mouse xenograft models to determine the underlying mechanism in vitro and in vivo. We demonstrate that levels of DNA methyltransferase 3 beta (DNMT3b) are significantly correlated with the OCT4 levels in HCC tissues (n = 144), and the OCT4 expression levels are positively associated with the serum IL-6 levels. Higher levels of IL-6, DNMT3b, or OCT4 predicted early HCC recurrence and poor prognosis. We show that IL-6/STAT3 activation increases DNMT3b/1 and OCT4 in HCC. Activated phospho-STAT3 (STAT-Y640F) significantly increased DNMT3b/OCT4, while dominant negative phospho-STAT3 (STAT-Y705F) was suppressive. Inhibiting DNMT3b with RNA interference or nanaomycin A (a selective DNMT3b inhibitor) effectively suppressed the IL-6 or STAT-Y640F-induced increase of DNMT3b-OCT4 and ALDH activity in vitro and in vivo. The fact that OCT4 regulates the DNMT1 expressions were further demonstrated either by OCT4 forced expression or DNMT1 silence. Additionally, the DNMT3b silencing reduced the OCT4 expression in sorafenib-resistant Hep3B cells with or without IL-6 treatment. Notably, targeting DNMT3b with nanaomycin A significantly increased the cell sensitivity to sorafenib, with a synergistic combination index (CI) in sorafenib-resistant Hep3B cells. The DNMT3b plays a critical role in the IL-6-mediated OCT4 expression and the drug sensitivity of sorafenib-resistant HCC. The p-STAT3 activation increases the DNMT3b/OCT4 which confers the tumor early recurrence and poor prognosis of HCC patients. Findings from this study highlight the significance of IL-6-DNMT3b-mediated OCT4 expressions in future therapeutic target for patients expressing cancer stemness-related properties or sorafenib resistance in HCC.